Pembiayaan Pasien COVID-19 dan Dampak Keuangan terhadap Rumah Sakit yang Melayani Pasien COVID-19 di Indonesia Analisis Periode Maret 2020 – Desember 2020 - Ambarwati, Wiwi (UI Scholars Hub, 2021)
Hospital visit volumes decline to 50% during the COVID-19 pandemic, which has reduced hospital revenue. The burden of hospitals handling COVID-19 patients is getting higher due to the late payment of COVID-19 claims. This study aims to review COVID-19 payment regulation in hospitals, constraints of policy implementation, and hospital financial challenges in Indonesia. This is a descriptive-analytic study, data collection is carried out through literature searches from scientific journals, BPJS Kesehatan, the Ministry of Health, Hospital Associations, and scientific seminars in online mass media. BPJS Kesehatan data as of 28 January 2020 shows, number of COVID-19 claims was 433,077 and from verification result found 266,737 (61.59%) eligible claims equivalent to 17.3 trillion, 165,189 dispute claims (38.14%) at 9.7 trillion, and 1,151 claim were not suitable (0.27%). Up to December 2020, the total claim submitted was Rp. 22.9 trillion, payment delivered to the hospitals was Rp. 14.5 trillion (63,3%) and the remaining unpaid was Rp. 8.4 trillion (36,6%). The challenges on COVID-19 claims include; claim payment was not made on time, a high number of dispute claims due to perceptual differences on the claims regulation, incomplete claim documents requirement, unpreparedness of dispute instrument tools, and a limited number of verifiers from the Ministry of Health to re-verify. The decrease in cash flow resulted in hospital operational obstacles, including; inability to pay obligations to drug and medical device vendors, and also payment of salaries for health workers and hospital staff.